Environment of the Early Pleistocene Banshan Paleolithic Site in the Nihewan Basin, North China - Yang, Jiaxing; Zhang, Zhen; Li, Yuecong; Wang, Fagang; Fan, Baoshuo; She, Zijing; Xie, Hongli; Wang, Siyu; Da, Shuoqiang (Frontiers in Earth Science, 2022)
Abstract： The Banshan archaeological site is one of the most important Early Pleistocene Paleolithic sites in the Nihewan Basin in North China. Based on analyses of pollen, grain size and charcoal of 56 samples from a sedimentary profile, we reconstructed the environment of the Banshan site before and after the interval of hominin activity (1.340–1.290 Ma). The results show that before the appearance of hominin activity (1.340–1.324 Ma), the climate of the region was initially cold and wet and then cold and dry. The regional vegetation was mainly Pinus and Picea forest in the earlier stage, and steppe dominated by arid-tolerant plants such as Artemisia and Chenopodiaceae in the later stage. During the period of hominin activity (1.324–1.318 Ma), the climate was warm and wet, the vegetation was mainly Pinus forest, and the site was a lakeside environment which would have provided resources such as food and water for hominins. During 1.318–1.310 Ma, the climate was warm and wet, the lake continued to expand and the lake level rose, which may have forced the hominins to migrate outside the area. During 1.310–1.290 Ma, the climate changed from warm and humid to cold and arid, accompanied by the change of the regional vegetation from forest to forest-grassland. Hominin activity at the Banshan site occurred during the interval of climate change from cold and dry to warm and wet, and it ended with the rise of the ancient lake level at Nihewan and the deterioration of the climate.